Danish Sailors, 1570-1870 - Johansen, Hans Chr. (M/S Museet for Søfarts årbog, 2017)
In the field of maritime research many books and articles have been written on single topics in Danish Maritime History. Hoiuever, when it comes to complete works, not a single complete work has abbeared since 1919. apart from »Dansk Søfartshistorie« (Danish Maritime History) in seven volumes which is being published at the present time. The previous literature has covered almost every subject in Danish maritime history, but one subject which perhaps has been slightly neglected is the sailors themselves.